2013
DOI: 10.2174/1381612811319080014
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Vaccines as an Option for Preventing Cervical Malignancies: (How) Effective and Safe?

Abstract: We carried out a systematic review of HPV vaccine pre- and post-licensure trials to assess the evidence of their effectiveness and safety. We find that HPV vaccine clinical trials design, and data interpretation of both efficacy and safety outcomes, were largely inadequate. Additionally, we note evidence of selective reporting of results from clinical trials (i.e., exclusion of vaccine efficacy figures related to study subgroups in which efficacy might be lower or even negative from peer-reviewed publications)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…Instead, what the clinical trials have shown is that HPV vaccines can prevent some of the pre-cancerous CIN 2/3 lesions associated with HPV-16 and HPV-18 infection, a large fraction of which would spontaneously resolve regardless of the vaccination status [2-4]. For example, in adolescent women aged 13 to 24 years, 38% of CIN 2 resolve after one year, 63% after two and 68% after three years [5].…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, what the clinical trials have shown is that HPV vaccines can prevent some of the pre-cancerous CIN 2/3 lesions associated with HPV-16 and HPV-18 infection, a large fraction of which would spontaneously resolve regardless of the vaccination status [2-4]. For example, in adolescent women aged 13 to 24 years, 38% of CIN 2 resolve after one year, 63% after two and 68% after three years [5].…”
Section: Lettermentioning
confidence: 99%
“…[7] CIN 2 is the least reproducible of all histopathologic diagnoses and may in part reflect sampling error. While CIN 3 is a more reliable marker for cancer progression than CIN 2, the use of this marker is not without caveats [2,10]. …”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse reactions as serious as permanent disability or even death (139 deaths so far) [2] are likely to result from the aluminium adjuvant that accumulates in the central nervous system. [3] The goal -the prevention of cervical cancer -remains to be proven. Finally, the two existing vaccines 'protect' only against two out of ten or more high-risk HPV types.…”
Section: Hpv Vaccine: Why the Rush?mentioning
confidence: 99%
“…Finally, the two existing vaccines 'protect' only against two out of ten or more high-risk HPV types. [3][4][5][6][7] Ever since gaining Food and Drug Administration approval in 2006, Merck has been heavily criticised in the USA for their overly aggressive lobbying campaigns and marketing strategies. [4] Further, the vast majority of publications on the topic have been authored by Merck or GlaxoSmithKline (GSK) employees, or researchers employed by or funded by these companies.…”
Section: Hpv Vaccine: Why the Rush?mentioning
confidence: 99%